The military and democracy in Indonesia : challenges, politics, and power - Rabasa, Angel; Haseman, John B. (RAND, 2002)
The Indonesian military, with its tradition of secular nationalism, is one of the few institutions that cut across the divides of Indonesian society. As it continues to play a critical part in determining Indonesia's future development, the military itself is undergoing profound change. The authors of this book explore the role of the military in politics and society since the fall of President Suharto in 1998. They examine key research issues that are central to the strategic interests of the United States in Asia: Will the Indonesian military be a constructive force supporting democratic processes or will it opt for authoritarian solutions? What are some realistic goals for further progress on military reform? And how can the United States engage the Indonesian military most effectively to help bring about positive change? To answer these questions, the authors present several strategic scenarios for Indonesia, each of which has important implications for U.S.-Indonesian relations, and propose goals for Indonesian military reform and elements of a U.S. engagement policy.